Infections in Surgery Prevention and Management - Bartoli, Stefano; Cortese, Francesco; Sartelli, Massimo; Sganga, Gabriele; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
Infections in surgery, commonly known as surgical site infections (SSIs), are complications that may occur after a surgical procedure. SSIs represent a serious problem leading to increased morbidity, mortality, and healthcare costs, highlighting the need for continued efforts to improve surgical practices and reduce their incidence. Several factors can contribute to the development of SSIs: patient-related factors (such as obesity, advanced age, diabetes, immunosuppression, pre-existing infections etc.); preoperative preparation-related factors (such as incomplete skin antisepsis or failure to administer appropriate antibiotic prophylaxis); microbial contamination (despite sterile techniques, microorganisms can infect the surgical site); surgical procedure-related factors (duration and complexity of the surgeries); postoperative care-related factors (such as inadequate wound care or infection control measures). To prevent SSIs, healthcare facilities implement various strategies, including: optimization of patients$1 (Bconditions before surgery; preoperative antibiotic prophylaxis; strict sterile technique; postoperative wound care; surveillance and monitoring to identify and address SSIs early, preventing their spread and complications. Despite the evidence supporting the effectiveness of best practices, many clinicians fail to implement them, and evidence-based practices that optimize both the prevention and treatment of SSIs tend to be underused, highlighting the importance of ongoing research and improvement in surgical techniques and infection control practices. This open access book provides a practical toolkit for surgeons and intensivists to improve their daily clinical practices in order to reduce the risk of SSIs.s
1. Guidelines and Good Clinical Practice in Surgical Infection -- 2. Impact of Healthcare-Associated Infections in Surgery -- 3. Epidemiological Framework: The Role of Surveillance -- 4. Measuring and Improving Care in Surgical Site Infections -- 5. Principles of Infection Prevention and Control in Surgery -- 6. Multimodal Approach to Implement Infection Prevention and Control in Surgery -- 7. Antimicrobial Stewardship in Surgery -- 8. Principles for Correct Surgical Antibiotic Prophylaxis and Antibiotic Therapy -- 9. Microbiological Diagnosis in the Era of Antimicrobial Resistance -- 10. Infection Prevention and Control in Acute Care Surgery -- 11. Intra-Abdominal Infections -- 12. Necrotizing Soft Tissue Infections -- 13. Invasive Candidiasis in Surgery -- 14. Source Control -- 15. Infection Control in Prosthetic Surgery -- 16. Surgical Wounds: Principles of Postoperative Care -- 17. Critically Ill Surgical Patients in the Intensive Care Unit -- 18. Synergy Between Infection Prevention and Control and Enhanced Recovery After Surgery -- 19. Patient Blood Management and Infection Prevention and Control -- 20. Financial Impact of Surgical Site Infections in Italy -- 21. The Legal Impact of Infections in Surgery Under Italian Law -- 22. The Strategic Role of Health Technology Assessment Within the Surgical Infection Setting.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Surgery; Anesthesiology; Critical care medicine; Medical microbiology; Surgery; Anesthesiology; Intensive Care Medicine; Medical Microbiology